Analysis Of Knowledge And Perceptions About The Dangers Of Hypertension With Prevention Behaviors Of Hypertension Complications In The Elderly At Wahyu Husada Gurah Clinic - Kurniawan Edi Priyanto; Fambudi Bima Sena Huda (Journal of Health Science Community, 2023)
Hypertension is a non-communicable disease that can become a big and serious problem because of the high prevalence of hypertension and tends to increase. The purpose of this study was to analyze the relationship between knowledge and perceptions about the dangers of hypertension with behavior to prevent complications of hypertension in the elderly at the Wahyu Husada Gurah Clinic. The design of this study was a quantitative observational study with a cross-sectional approach with a research focus aimed at analyzing the relationship between knowledge and perceptions about the dangers of hypertension and behavior to prevent complications of hypertension in the elderly at the Wahyu Husada Gurah Clinic. Total population of 86 respondents and a sample of 71 respondents were taken by Simple Random Sampling technique. The findings found that almost half of the respondents had moderate category knowledge of 31 respondents (44%). Nearly half of the respondents had a sufficient category perception of 32 respondents (45%). Almost half of the respondents had less category behavior as many as 30 respondents (42%). Based on the results of the Spearmen Rank analysis it showed that the knowledge variable had a p-value of 0.008 and the perception variable had a p-value of 0.001 <0.05, so H1 was accepted so it was concluded that partially there is a relationship between knowledge and perceptions about the dangers of hypertension with behavior to prevent complications of hypertension in the elderly at the Wahyu Husada Gurah Clinic.